Infants' Understanding and Production of Goal-Directed Actions in the Context of Social and Object-Related Interactions - Daniela Corbetta (Frontiers Research Topics, 2017)
Since the discovery of mirror neurons, the study of human infant goal-directed actions and object manipulation has burgeoned into new and exciting research directions. A number of infant studies have begun emphasizing the social context of action to understand what infants can infer when looking at others performing goal-directed actions or manipulating objects. Others have begun addressing how looking at actions in a social context, or even simply looking at objects in the immediate environment influence the way infants learn to direct their own actions on objects. Researchers have even begun investigating what aspects of goal-directed actions and object manipulation infants imitate when such actions are being modeled by a social partner, or they have been asking which cues infants use to predict others' actions. A growing understanding of how infants learn to reach, perceive information for reaching, and attend social cues for action has become central to many recent studies. These new lines of investigation and others have benefited from the use of a broad range of new investigative techniques. Eye-tracking, brains imaging techniques and new methodologies have been used to scrutinize how infants look, process, and use information to act themselves on objects and/or the social world, and to infer, predict, and recognize goal-directed actions outcomes from others. This Frontiers Research topic brings together empirical reports, literature reviews, and theory and hypothesis papers that tap into some of these exciting developmental questions about how infants perceive, understand, and perform goal-directed actions broadly defined. The papers included either stress the neural, motor, or perceptual aspects of infants' behavior, or any combination of those dimensions as related to the development of early cognitive understanding and performance of goal-directed actions.